KEWENANGAN PENGAWASAN PEMERINTAH PROVINSI TERHADAP PENYELENGGARAAN PEMERINTAHAN KABUPATEN/KOTA BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Arie Elcaputera (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2021)
Abstract: The Republic of Indonesia is a unitary state which in the implementation of governance in the regions is based on the principle of decentralization. Then this principle gave birth to the meaning of autonomy with the substance of the transfer of authority in the implementation of government in the regions. The district / city government in carrying out its government based on the principle of autonomy, does not rule out fraud or violations both in carrying out its duties and authorities and in making district / city regional policies, because in the current era of regional autonomy, there is a tendency for autonomy to be interpreted as regional freedom to do anything without intervention from the Governor as the representative of the central government in the regions.The purpose of research is to determine the supervisory authority and the provincial government's supervisory model for regency / city administration based on law number 23 of 2014 concerning regional governance. This is the normative law research. The results showed that the central government's supervisory function was present to prevent conflicts between authorities. Supervision from the central government to local governments is commonly carried out in the form of preventive supervision and repressive supervision. Considering this, so this is the importance of supervision from the provincial government to the administration of district / city governments in order to strengthen the implementation of regional autonomy in accordance with the mandate and objectives of regional autonomy. Keywords: Authority; Control; Local government